2020
DOI: 10.1080/13696998.2019.1707210
|View full text |Cite
|
Sign up to set email alerts
|

Living with ulcerative colitis in Germany: a retrospective analysis of dose escalation, concomitant treatment use and healthcare costs

Abstract: Aims: To investigate treatment of moderate-to-severe ulcerative colitis (UC) using real-world German health insurance claims data. Materials and methods: A retrospective, longitudinal cohort study was conducted from a German statutory health insurance database for adult patients with UC indexed on biologic therapy initiation (2013-2015). Anonymized data were evaluated for 12 months prior to (baseline) through 24 months after (follow-up) indexing. Biologic dose escalations, steroid and immunosuppressant use, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 47 publications
0
37
0
Order By: Relevance
“…Approximately half of patients used an IM with a TNFi in follow-up, slightly higher than the 41% of patients who used an IM with biologic therapy in an equivalent study of German patients [28]. Steroid use with a TNFi was substantially lower (<5%) than was observed among German patients when accounting for steroid tapering (25%) [28].…”
Section: Discussion/conclusionmentioning
confidence: 82%
See 1 more Smart Citation
“…Approximately half of patients used an IM with a TNFi in follow-up, slightly higher than the 41% of patients who used an IM with biologic therapy in an equivalent study of German patients [28]. Steroid use with a TNFi was substantially lower (<5%) than was observed among German patients when accounting for steroid tapering (25%) [28].…”
Section: Discussion/conclusionmentioning
confidence: 82%
“…Data collected during the 2 years prior to the index date (baseline period) and the 2 years after the index date (follow-up period) were evaluated. This study is one of two studies conducted to describe real-world outcomes in patients with UC, and the other to describe health-care resource utilization (HCRU) and treatment patterns among patients with UC in Germany [28] (shown in Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…There were 9 reports of dose escalation done to address LOR, 31 , 44 , 46 , 63 , 66–68 , 75 , 76 whereas the remaining 39 dose escalations were done for any reason ( Figure 2 ). 22–29 , 32 , 34 , 35 , 37 , 38 , 40–42 , 45 , 47–52 , 55 , 57–62 , 64 , 65 , 69 , 71 , 72 , 74 The average rate of escalation by dose increase varied greatly, ranging from 80% to 340% relative to the starting dose ( Supplementary Table 5 ). 26 , 29 , 31 , 35 , 36 , 38 , 40 , 46 , 49 , 52 , 57 , 59 , 61–63 , 65–69 , 75 In studies with follow-up times of ≤12 months, the rate of dose escalation was 11.5–44%, whereas in studies with follow-up times of >12-≤24 months and >24 months, the rate of dose escalation was 8.4–73.5% and 4.9–54.0%, respectively ( Supplementary Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five systematic reviews were identified, 6 10 and 81 case series selected and listed on Table 2 11 …”
Section: Results – Dose Intensificationmentioning
confidence: 99%